2014
DOI: 10.21608/jpp.2014.64669
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF SEAWEED EXTRACT AND AMINO ACIDS ON GROWTH AND PRODUCTIVITY AND SOME BIOCOSTITUENTS OF COMMON BEAN (Phaseolus vulgaris L) PLANTS

Abstract: Two filed experiments were carried out at a private farm in Behaira Governorate, Egypt during 2012 and 2013 summer seasons. Experiments aimed to study the effect of two widely marketing (commercial safe compounds). First, is a seaweed extract (with commercial name of sea weed) at 1, 2 and 4 ml/l while the second is a mixture of free amino acids (with plant origin and commercially name is sway) at 2,4and 8 ml/l and seaweed at 2 ml/l + amino acids at 4 ml/. The two compounds were applied as foliar spray three ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 7 publications
(10 reference statements)
6
29
1
Order By: Relevance
“…In our research, the use of biostimulants based on amino acids and seaweed extracts had a positive effect on the nutritional value of beans by increasing their protein content. Application of seaweed extract and amino acids had a positive effect on increasing the protein content in bean, pea, and faba bean seeds [59,71,74,78,80]. This was confirmed by Rouphael [62]; in their research, the increase in protein content in spinach plants was obtained after using biostimulants containing an extract of Ecklonia maxima and Ascophyllum nodosum and legume-derived protein hydrolysate.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In our research, the use of biostimulants based on amino acids and seaweed extracts had a positive effect on the nutritional value of beans by increasing their protein content. Application of seaweed extract and amino acids had a positive effect on increasing the protein content in bean, pea, and faba bean seeds [59,71,74,78,80]. This was confirmed by Rouphael [62]; in their research, the increase in protein content in spinach plants was obtained after using biostimulants containing an extract of Ecklonia maxima and Ascophyllum nodosum and legume-derived protein hydrolysate.…”
Section: Discussionmentioning
confidence: 84%
“…Use of extracts from Kappaphycus alvarezii and A. nodosum increased the number of pods, seeds, and yield in soybean [68,69], even under stress conditions (reduced NPK fertilization) [70]. Bean plants reacted favorably to the foliar application of Caulerpa racemosa and A. nodosum extract by increasing the number of pods and seeds, one thousand weight of bean, and seed yield in common beans [71,72], mung beans [73], and broad beans [74].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, many parameters of vegetative growth as well as plant yield, nutrient content and fruit quality were improved by application of these three commercial organic fertilizers (Souri and Aslani 2018). Common bean grown in North West delta showed positive and significant effect of seaweed extract applied solely or in combination with amino acids where the highest yield and yield components as well as the harvest index were detected at harvest time (Zewail, 2014).…”
Section: Fresh and Dry Weightsmentioning
confidence: 99%
“…Under Egyptian conditions, Zewail, (2014) found that nitrogen, phosphorus and potassium concentrations in common bean leaves were highly significantly increased with addition of seaweed extract combined with amino acids (2 m l -1 seaweed + 4 ml l -1 amino aicds).…”
Section: Nitrogen Phosphorus and Potassium Uptakementioning
confidence: 99%